2012
DOI: 10.1037/a0028542
|View full text |Cite
|
Sign up to set email alerts
|

Psychoanalytic witnessing: Professional obligation or moral imperative?

Abstract: In this response to Leanh Nguyen's paper, I ask whether psychoanalytic witnessing is a professional obligation or a moral imperative. Describing the increasing number of psychodynamic clinicians who take their psychoanalytic knowledge out of the traditional setting and apply it to a variety of situations that call for an active commitment to social justice and human rights, of which Dr. Nguyen is a prime example, I argue that as clinicians we are morally obligated to bear witness when an external event has cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Their findings indicated that most therapists and clients shared, either implicitly or explicitly, their political views with each other in psychotherapy, and that a stronger therapeutic alliance was associated with perceived political similarity with the therapist, implicit political disclosure of the therapist, and helpful political discussions in therapy. The findings are consistent with clinical evidence that sociopolitical issues are an inextricable part of the therapeutic process (Ainslie, 2011; Boulanger, 2012; Ipp, 2010; Tummala-Narra, 2015; Yi, 2014). Yet, therapists contend with questions concerning how to engage with sociopolitical context and the timing of these discussions with their clients.…”
Section: Psychoanalytic Psychotherapy In the Present Sociopolitical C...supporting
confidence: 86%
See 1 more Smart Citation
“…Their findings indicated that most therapists and clients shared, either implicitly or explicitly, their political views with each other in psychotherapy, and that a stronger therapeutic alliance was associated with perceived political similarity with the therapist, implicit political disclosure of the therapist, and helpful political discussions in therapy. The findings are consistent with clinical evidence that sociopolitical issues are an inextricable part of the therapeutic process (Ainslie, 2011; Boulanger, 2012; Ipp, 2010; Tummala-Narra, 2015; Yi, 2014). Yet, therapists contend with questions concerning how to engage with sociopolitical context and the timing of these discussions with their clients.…”
Section: Psychoanalytic Psychotherapy In the Present Sociopolitical C...supporting
confidence: 86%
“…As a racial minority woman, at times, I fluctuate between feeling frustrated with accommodating others who do not know nearly as much about my sociocultural world as I know about theirs, and recognizing that all of us, regardless of race, coexist in a traumatic framework of race in U.S. society. The effects that racial and other forms of sociocultural trauma on the therapeutic process have been examined in depth by psychoanalytic scholars (Altman, 2010; Boulanger, 2012; Holmes, 2016; Yi, 2014). Yet, the current sociopolitical climate in the United States has made even more explicit the presence of sociocultural trauma in psychotherapy, calling for therapists to examine and reexamine the influence of their own interpersonal and social, cultural, and political histories on their approach to practice.…”
Section: Psychoanalytic Psychotherapy In the Present Sociopolitical C...mentioning
confidence: 99%
“…Boulanger (2012) feels that “as clinicians we are ‘morally obligated’ to bear witness when certain external acts or events transgress human values and cause ‘psychic distress’ to our clients. Without validation, the client may doubt the significance and legitimacy of her experience” (p. 318).…”
Section: Therapy As “Shock Absorber”mentioning
confidence: 99%
“…Moreover, for research to touch upon dissociated pains and detached truisms, the questions must be asked within a caring and compassionate relationships. For professional witnessing (Boulanger, 2007(Boulanger, , 2012 to overcome trauma-induced repression and dissociation, and at the same time to avoid eliciting further trauma, it must be conducted with utmost care and sensitivity.…”
Section: At the Benchmentioning
confidence: 99%